Tantangan Ketidakseimbangan Kerja dan Lemahnya Serikat Buruh di Tengah Target Ekonomi Nasional : Penelitian - Putri Elviana Indah Sari; Muhammad Ichsan Chabibi; Salsabila Helena Diah; Bagus Tri Prasetyo; Tegar Harbriyana Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Indonesia's high-growth-oriented economic development often neglects workers' welfare, triggering an imbalance between work and personal life, exacerbated by the weakening role of labor unions, which reduces workers' bargaining power. This paper analyzes the challenges of work-life imbalance and the weakness of labor unions, and their impact on labor productivity and sustainable economic growth. The method used is normative legal writing with a legislative, conceptual, and literature study approach. The analysis includes labor regulations, productivity data, the gender wage gap, and the dynamics of industrial relations in Indonesia. The results show that work imbalance is triggered by a culture of long working hours, a time-based appraisal system, and job instability due to outsourcing, while the weakness of labor unions is caused by organizational fragmentation, political influence, and a lack of leadership. This paper recommends strengthening labor unions, enforcing labor laws, reforming productivity measurements, gender equality policies, and tripartite social dialogue to achieve inclusive and sustainable economic growth.